2022
DOI: 10.3390/life12121997
|View full text |Cite
|
Sign up to set email alerts
|

Total Facial Autologous Fat Grafting for Treating Skin Manifestations in Scleroderma

Abstract: Systemic sclerosis (SSc) or scleroderma, is a rare, systemic autoimmune connective tissue disease that can cause fibrosis of cutaneous tissue and visceral organs. Facial involvement can have a deleterious effect on patients’ function, cosmetic appearance and quality of life. This study describes our experience and results with total facial autologous fat grafting for treating scleroderma. It includes 14 women and 3 men with SSc, at an average age of 51.3 years who underwent 32 autologous fat grafting surgeries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Studies have shown an improvement in the aesthetic appearance, along with a significant effect on tissue elasticity and pliability. This modality has also been shown to increase the size of the oral opening [43]. The use of fat grafting over multiple procedures permitted the injection of increased volumes due to improved facial elasticity [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown an improvement in the aesthetic appearance, along with a significant effect on tissue elasticity and pliability. This modality has also been shown to increase the size of the oral opening [43]. The use of fat grafting over multiple procedures permitted the injection of increased volumes due to improved facial elasticity [43].…”
Section: Discussionmentioning
confidence: 99%
“…This modality has also been shown to increase the size of the oral opening [43]. The use of fat grafting over multiple procedures permitted the injection of increased volumes due to improved facial elasticity [43]. Evidence regarding fat grafting and improvements in the oral aperture is thought to be due to various mechanisms and tissue regeneration [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The topic of SSc orofacial manifestations has also been addressed in a retrospective study conducted by Berl et al, in which the authors described their experience and results with total facial autologous fat grafting in SSc patients. To perform this, the authors had made use of a technique consisting of the subcutaneous injection of fat in all regions of the face, including the superficial temporal fascia and superficial muscular aponeurotic system [ 11 ]. In the treated SSc patients, the oral opening increased by an average of 33%, and all of them reported improvement in quality of life and satisfaction with the aesthetic outcomes [ 11 ].…”
mentioning
confidence: 99%
“…To perform this, the authors had made use of a technique consisting of the subcutaneous injection of fat in all regions of the face, including the superficial temporal fascia and superficial muscular aponeurotic system [ 11 ]. In the treated SSc patients, the oral opening increased by an average of 33%, and all of them reported improvement in quality of life and satisfaction with the aesthetic outcomes [ 11 ]. Interestingly, patients who underwent multiple surgeries were able to be injected with increasing amounts of fat over time, indicating that the treatment may led to improved facial tissue elasticity [ 11 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation